2005
DOI: 10.1017/s0030605305000438
|View full text |Cite
|
Sign up to set email alerts
|

Responding to forest degradation: altered habitat use by Dian's tarsier Tarsius dianae in Sulawesi, Indonesia

Abstract: As most of the pristine forests of South-east Asia have been lost, the ability of its animal species to coexist with humans becomes increasingly important. Dian's tarsier Tarsius dianae, one of the smallest primates, lives in forests of central Sulawesi, Indonesia that are experiencing a dramatic increase in degradation by humans. To evaluate the effects of anthropogenic disturbance on tarsiers we used a comprehensive approach to estimate habitat suitability for these nocturnal insecthunters. On four study plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 33 publications
(31 reference statements)
3
56
0
1
Order By: Relevance
“…We captured 2 males with T. lariang-typic genetic signatures several hundred meters outside of their species' usual range. This observation falls into a radius that tarsiers easily cover within a single night (42,47). Although these 2 individuals might also have been translocated and released pets, the steep gradients in allele frequencies at the species boundary and the consistent lack of alien genes in the reference populations suggest that accidental introductions do not play an important role in shaping the genetic structure of tarsier populations in a human-altered landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We captured 2 males with T. lariang-typic genetic signatures several hundred meters outside of their species' usual range. This observation falls into a radius that tarsiers easily cover within a single night (42,47). Although these 2 individuals might also have been translocated and released pets, the steep gradients in allele frequencies at the species boundary and the consistent lack of alien genes in the reference populations suggest that accidental introductions do not play an important role in shaping the genetic structure of tarsier populations in a human-altered landscape.…”
Section: Discussionmentioning
confidence: 99%
“…This interspecific difference could be a signature of a more recent population expansion of Dian's tarsiers to populate the eastern areas of central Sulawesi. Judging from this species' wide distribution (41), its adaptability to human land use (42), and the presumed displacement of T. lariang by T. dentatus in parts of its range (see below), Dian's tarsier appears to be a good disperser and probably the more opportunistic of the 2 species.…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation for lorises is that they are quadrupedal and are incapable of leaping, thus requiring canopy continuity to move easily throughout the forests, although they can move on Merker et al 2005). Populations in anthropo genically modified areas are considerably lower compared with other populations (Merker et al 2005). Such requirements pose a challenge for tarsiers when confronted with environmental and ecological changes.…”
Section: Microhabitat Variability and Niche Divergencementioning
confidence: 99%
“…Past studies on slow lorises have found that they occupy numerous types of environment, from plantations and other agricultural areas to heavily degraded forests and pristine forests (Elliot & Elliot 1967, Wiens & Zitzmann 2003, Radhakrishna et al 2006). An important limitation for lorises is that they are quadrupedal and are incapable of leaping, thus requiring canopy continuity to move easily throughout the forests, although they can move on Merker et al 2005). Populations in anthropo genically modified areas are considerably lower compared with other populations (Merker et al 2005).…”
Section: Microhabitat Variability and Niche Divergencementioning
confidence: 99%
“…A major goal of primatology is to document important primate resources and to understand how these resources influence primate behavior and population dynamics [e.g., Merker et al, 2005;Irwin, 2008;Fish, 2014;Chapman et al, 2015]. Most research focuses on food resources [e.g., Ganzhorn et al, 2004;Balko and Underwood, 2005;Joly and Zimmermann, 2007;Yamashita et al, 2010].…”
Section: Introductionmentioning
confidence: 99%